Efektivitas Sanksi Terhadap Pelanggar Marka Jalan Berdasarkan Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan Oleh Kepolisian Resor Kota Pekanbaru - Putri, Ayu Yohana; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
When the road users violating the provisions on road markings, the existing sanctionsshould be given to him, in accordance with Article 287 paragraph (1) of Law No. 22 of 2009 onRoad Traffic and Road Transport, which is subject to a fine and imprisonment, even if it is set toapplicable law, does not make citizens wary violate road markings. So the traffic is orderly, safeand convenient can not be implemented. In this case relates to the effectiveness of sanctionsagainst offenders Marka Jalan Based on Law No. 22 of 2009 on Road Traffic and RoadTransport By Pekanbaru City Police. The purpose of writing this essay that the first, theeffectiveness of sanctions against violators of road markings based on Law No. 22 of 2009 onRoad Traffic and Road Transport By City Police Pekanbaru, second, obstacles in theimplementation of sanctions against violators of road markings based on Law No. 22 of 2009 onRoad Traffic and Road Transport By Pekanbaru City Police, the third, the efforts made toovercome bottlenecks in the imposition of sanctions pursuant to Law No. 22 of 2009 on RoadTraffic and Road Transport By Pekanbaru City Police.This type of research can be classified into types of juridical sociological research,because in this study the authors directly conduct research on a study in order to give a completeand clear picture of the problems examined. This study was performed in Pekanbaru City Police,while the overall population and the sample is related to the issues examined in this study, thedata source used, primary data, secondary data and data tertiary data collection techniques inthis study with observation, questionnaire , interview and literature study.From the research there are three basic problems that can be inferred. first, theeffectiveness of sanctions against violators of road markings based on the Law on Road Trafficand Road Transport By Pekanbaru City Police law enforcement have been implementedalthough there are still violations of road markings. second, obstacles in the implementation ofsanctions against violators of road markings based on the Law on Road Traffic and RoadTransport By Pekanbaru City Police are factors of law enforcement, public awareness andinfrastructure, the third, the efforts made to overcome obstacles in sanctioning by Law on RoadTraffic and Road Transport By Pekanbaru City Police that law enforcement should be moreprofessional, dissemination to the public to be aware of law, improve facilities andinfrastructure. Suggestions writer, first, the expected sanctions against violators of roadmarkings should be emphasized, second obstacle is the reason for not efektivnya enforcement ofsanctions against violators of road markings not become a reason. Third, efforts made mustcontinue to be implemented, in order to create traffic enforcement.Keywords: Effectiveness - Marka - Road - Traffic - Police.